LONGAN COFFEE MADE OF LONGAN FRUIT SEED WASTE FROM BOROBUDUR (SNMIPA, 2019)
The purpose is Utilizing the longan seeds be raw material of coffee drinks and finding the similarities to the regular coffee drinks. History records that the discovery of coffee as a nutritious and energized drink was first discovered by the Ethiopians in the African continent about 3000 years (1000 BC) ago. Coffee then continues to grow until now became one of the most popular drinks in the world consumed by various circles of Indonesia itself and it has been able to produce more than 400 thousand tons of coffee per year. Place and Time of study Venue: Science Laboratory, SMA Negeri 1 Grabag. Time: SeptemberOctober 2017. Research Procedures. The method used in this study is to use the method of Experiment and Interview / Questionnaire. The experimental stages are: 1. Experiment I 2. Experiment II Organoleptic Test Seed waste can be processed into coffee with low caffeine content and rich in antioxidants. From the results of organoleptic test, this coffee is resemble to arabica and robusta coffee. So that the waste seed of longan can be processed into a more useful product that is Longan Coffee.